2014
DOI: 10.1155/2014/164039
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Approach for Predicting the Rate of Frequency Change of Notched Beam Exposed to Gaussian Random Excitation

Abstract: During fatigue damage accumulation, cracks propagate through the material leading to catastrophic failure. As the cracks propagate, the natural frequency lowers, leading to a changing stress state. A new method has been developed where the damage accumulation rate is computed in the frequency domain using Linear Elastic Fracture Mechanics (LEFM), stress intensity, and the natural frequency. A finite element model was developed to predict the stress intensity and natural frequency during damage accumulation. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…After the location of the crack, an inverse method inspired from the literature is used to estimate the crack depth [34]. First, the localized crack position is used to plot one of the frequencies as function of the crack depth.…”
Section: Crack Quantificationmentioning
confidence: 99%
“…After the location of the crack, an inverse method inspired from the literature is used to estimate the crack depth [34]. First, the localized crack position is used to plot one of the frequencies as function of the crack depth.…”
Section: Crack Quantificationmentioning
confidence: 99%
“…The presence of cracks in a structure is usually detected by adopting a linear approach through the monitoring of changes in the structure's dynamic response features [27][28][29]. Several studies have reported analytical and experimental results for vibration of cracked Euler-Bernoulli beams and the effects of surface cracks on fundamental frequencies and vibration modes of beams [30][31][32]. Few researchers uncovered nonlinear dynamic behavior of beam structures with single crack in the time history and frequency spectrum [33][34][35].…”
Section: Nonlinear Dynamics Of Undamaged and Damaged Structuresmentioning
confidence: 99%
“…The model applied linear elastic fracture mechanics for crack propagation and included the shift in frequency that resulted from the crack growth. Habtour et al [114] developed an FEM model to predict the stress intensity and natural frequency during damage accumulation. The analytical model developed by Paulus et al was coupled with the FEM to predict TTF for complex geometries for which stress intensity values were not available.…”
Section: Uniaxial Loadingmentioning
confidence: 99%